2016
DOI: 10.1007/s10522-016-9641-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in older age: perspectives for healthy ageing and frailty

Abstract: Regular physical activity helps to improve physical and mental functions as well as reverse some effects of chronic disease to keep older people mobile and independent. Despite the highly publicised benefits of physical activity, the overwhelming majority of older people in the United Kingdom do not meet the minimum physical activity levels needed to maintain health. The sedentary lifestyles that predominate in older age results in premature onset of ill health, disease and frailty. Local authorities have a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
714
5
93

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 972 publications
(833 citation statements)
references
References 124 publications
(141 reference statements)
21
714
5
93
Order By: Relevance
“…It is well described in literature that muscle strength and power exercises are effective in improving muscle strength, mass and power, and the functionality, components that are closely related to the maintenance of functional independence and the ability to perform daily living activities in older adults [1][2][3] . However, it is estimated that the number of old participants who frequently practice strength training is less than 10% 4 and the low adherence may be related to the repetitive and tedious characteristics of this type of training, reported by participants 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well described in literature that muscle strength and power exercises are effective in improving muscle strength, mass and power, and the functionality, components that are closely related to the maintenance of functional independence and the ability to perform daily living activities in older adults [1][2][3] . However, it is estimated that the number of old participants who frequently practice strength training is less than 10% 4 and the low adherence may be related to the repetitive and tedious characteristics of this type of training, reported by participants 5 .…”
Section: Introductionmentioning
confidence: 99%
“…El sobrepeso y la obesidad se han convertido en problemas de salud pública que incluso han alcanzado a los adultos mayores (AM) (1,2), hecho que, sumado al desconocimiento sobre buenos hábitos de alimentación y actividad física (AF) (3)(4)(5)(6), podría suponer mayor riesgo por muerte cardiovascular futura (7). Al respecto, diversas investigaciones han descrito los beneficios conseguidos a través de programas de prevención de salud para AM (3,8), especialmente aquellos basados en iniciativas sobre educación alimentaria y la práctica regular de AF (4,9).…”
Section: Introductionunclassified
“…Al respecto, diversas investigaciones han descrito los beneficios conseguidos a través de programas de prevención de salud para AM (3,8), especialmente aquellos basados en iniciativas sobre educación alimentaria y la práctica regular de AF (4,9).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Physical activity tends to decrease with age. Studies reported that a decline in voluntary physical activity which is associated with reductions in several measures of cardiorespiratory fitness, including maximal aerobic capacity, muscle strength, and fatiguability leading to an increased risk of frailty (Mcphee et al, 2016). Also, reports from National Health and Morbidity Survey revealed that over the previous 30 years, there were progressive decreases in the level of physical activity among Malaysian population.…”
Section: Introductionmentioning
confidence: 99%